A simple treatment method for phenylarsenic compounds: Oxidation by ferrate (VI) and simultaneous removal of the arsenate released with in situ formed Fe(III) oxide-hydroxide - Xie, Xiande; Cheng, Hefa (Environment international, 2019)
p-Arsanilic acid (p-ASA) and roxarsone (ROX) are two major phenylarsenic feed additives that are still widely used in many countries, and the land application of animal waste containing these compounds could introduce large quantities of arsenic into the environment. In this study, we proposed a treatment scheme for animal waste that involves leaching of p-ASA/ROX out of the manure first by water, then oxidation by ferrate (Fe(VI)) and removal of the arsenate released by in situ formed Fe(III) oxide-hydroxide. The effects of solution pH, dosage of Fe(VI), solution ionic strength, and matrix species on the treatment performance were systematically evaluated. Initial solution pH values of 4.1 and 2.0 were chosen for the oxidation of p-ASA and ROX, respectively, while efficient arsenate removal could be achieved with relatively small adjustment of the final solution pH (to 4.0). The pH-dependent second-order rate constants for the reactions between ferrate and p-ASA and ROX over the pH range of 2.0–12.0 were estimated to be 7.13 × 105–2.01 × 10−1 and 8.91 × 103–1.65 × 10−1 M−1 s−1, respectively. The degradation pathways of p-ASA/ROX during ferrate oxidation were proposed based on the inorganic and organic intermediates identified. Depending on the levels of p-ASA/ROX, effective treatment could be achieved through flexible adjustment of the Fe(VI) dosage. p-ASA/ROX (10 mg-As/L) in swine manure leachate could be efficiently treated by ferrate oxidation within 5 min, with the overall arsenic removal efficiency higher than 99.2%. The treatment performance was barely affected by the presence of common ions (K+, Ca2+, Na+, Mg2+, SO42−, NO3−, and Cl−), while humic acid, Mn2+, Ni2+, Fe3+, and Co2+ inhibited p-ASA/ROX oxidation. The presence of PO43− and NH4+ could accelerate the oxidation of p-ASA/ROX, but PO43− and humic acid compromised sorptive removal of the released arsenate due to their competitive sorption on the Fe(III) oxide-hydroxide precipitate. Ferrate oxidation is green and fast, and the operation is simple, thus it could serve as a promising and environment-friendly option for mitigating the risk of phenylarsenic feed additives in animal waste. [Display omitted] •A simple method for treating p-ASA and ROX using ferrate (VI) was developed.•Kinetics and mechanism of p-ASA and ROX oxidation by ferrate (VI) were elucidated.•Arsenate released was removed through sorption onto the in situ formed FeO(OH).•The oxidation process took <5 min, and the total arsenic removal efficiency was >99%.•Ferrate treatment is a faster and more convenient alternative to Fenton process.